Simulation and Active Learning Decreases Training Time of an Emergency Triage Assessment and Treatment Course in Pilot Study in Malawi: Implications for Increasing Efficiency and Workforce Capacity in Low-Resource Settings. Issue 12 (28th December 2021) - Sigalet, Elaine L.; Lufesi, Norman; Dubrowski, Adam; Haji, Faizal; Khan, Rabia; Grant, David; Weinstock, Peter; Wishart, Ian; Molyneux, Elizabeth; Kissoon, Niranjan
Abstract : Objectives: The aim of the Emergency Triage Assessment and Treatment (ETAT) plus trauma course is to improve the quality of care provided to infants and children younger than 5 years. The curriculum was revised and shortened from 5 to 2.5 days by enhancing simulation and active learning opportunities. The aim of this study was to examine the feasibility and value of the new short-form ETAT course by assessing postcourse knowledge and satisfaction. Methods: We delivered the short-form ETAT course to a group of interdisciplinary health workers in Malawi. Precourse and postcourse knowledge was assessed using a standardized 20 questions short answer test used previously in the 5-day courses. A 13-statement survey with 2 open-ended questions was used to examine participant satisfaction. Results: Participants' postcourse knowledge improved significantly ( P < 0.001) after the shorter ETAT course. Participants reported high levels of satisfaction with the short-form ETAT. Conclusions: Simulation and other active learning strategies reduced training time by 50% in the short-form ETAT course. Participants with and without previous ETAT training improved their knowledge after participating in the short-form ETAT course. Reduced training time is beneficial in settings already burdened by scarce human resources, may facilitate better access to in-service training, and build capacity while conserving resources in low-resource settings.